An Ethylene Biosynthesis-Inducing Endoxylanase Elicits Electrolyte Leakage and Necrosis in Nicotiana tabacum cv Xanthi Leaves - Bailey, Bryan A. (1990)
We have previously demonstrated that a protein purified from xylan-induced culture filtrates of Trichoderma viride contains β-1,4-endoxylanase activity and induces ethylene biosynthesis in tobacco (Nicotiana tabacum cv Xanthi) leaf discs. When the ethylene biosynthesis-inducing xylanase (EIX) was applied to cut petioles of detached tobacco leaves, it induced ethylene biosynthesis within 1 hour and extensive electrolyte leakage and necrosis were observed in tobacco leaf tissue within 5 hours. Ethylene-pretreatment (120 microliters per liter ethylene for 14 hours) of tobacco leaves enhanced ethylene biosynthesis in response to EIX by more than threefold and accelerated development of cellular leakage and necrosis. In intact plants, similar symptoms could be induced in leaves that were distant from the point of the enzyme application. The evidence suggests that EIX is translocated via the vascular system and elicits plant responses similar to those observed in a hypersensitive response.